(untitled) (Annual Transactions of the Nordic Rheology Society, 2024)
Oil-based drilling fluids are often used to drill geothermal or petroleum wells in hot locations. These fluids normally consist of dispersion of organophilic clays in water-in-oil emulsions. If loss of fluid to the formation is expected, fibres or other additives for fluid loss prevention are added. In the present article results from a study showing the effects of the additions of weight materials and asphaltic resin-based fluid loss prevention additive on rheological properties of the drilling fluids are shown. These results show the complex behaviour of the mixture of these particulate materials into emulsions. Filtration control is measured in a pressure cell where the flow goes through filter paper with 11 and 22 microns opening.